Electrical and microstructural properties of Yb-doped CeO2 - B. Matović; M. Stojmenović; J. Pantić; A. Varela; M. Žunić; N. Jiraborvornpongsa; T. Yano (Journal of Asian Ceramic Societies, 2014)
Nanopowdered Ce1−xYbxO2−δ solid solutions (0 ≤ x ≤ 0.2) were synthesized by a self-propagating room temperature synthesis. XRD and SEM were used to study the properties of these materials as well as the Yb solubility in CeO2 lattice. Results showed that all the obtained powders were solid solutions with a fluorite-type crystal structure and with nanometric particle size. The average size of Ce1−xYbxO2−δ particles was approximately 3 nm. Electrochemical impedance spectroscopy for the sintered pellets depicted that it was possible to separate Rbulk and Rgb in the temperature interval of 550–800 °C. The activation energy for the bulk conduction was 1.03 eV and for grain boundary conduction was 1.14 eV. Grain boundary resistivity dominates over the other resistivities. These measurements confirmed that Yb3+-doped CeO2 material had a potential as electrolyte for intermediate-temperature solid oxide fuel cell applications.